STUDI KOMPARASI TENTANG EKONOMI PANCASILA DAN EKONOMI ISLAM - M. Sofyan Alnashr; Muzayyanah Muzayyanah (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2016)
Indonesia is a country that uses a system of Pancasila economy, the economic system imbued with the ideology of Pancasila which is a joint effort is based on familial and national mutual cooperation. When viewed in terms of religion embraced by its people, the majority of Indonesian people are Muslim. Therefore, should the principles contained in the Pancasila economy inclines to the principles of Islamic Economics. Principles of Islamic Economics leads to a goal for the welfare of society. In reality the people of Indonesia are still many who have not been prosperous. It becomes important to study because, according to some researchers are assuming the principles of Pancasila economy is not in accordance with the principles of Islamic Economics and of course it is not justified in view of the majority of Indonesian people are Muslim. This type of research is a library research qualitative, where the processing of the data is not based on calculation of statistics. Analysis of the data used in this study is a comparative analysis constant, which are placed as close watch on the results of the data reduction procedure or the processing of data in order to establish the reliability of building concepts, categories, generalization or with the overall findings of the study itself so'm really solid (match) with the data and the reality on the ground. The results showed that between Economy and Economic Pancasila Pancasila according Mubyarto according to Mohammed Abdul Mannan there are similarities in terms of principle, namely the principle of kinship and brotherhood. The principles applied in Indonesia in the form of cooperatives.